Analisis Strategi Pemasaran yang Efektif bagi Pengguna E- Commerce - Anisa Yusrin Nanda (Jurnal Manajemen dan Inovasi (MANOVA), 2018)
The development of world technology, information, and the internet more advanced and flourishing from time to time. The impact of the development of the world of such technology can be felt by most people from the start of the simple to modern and fast-paced so as to the business. To market their business quickly and precisely, businesses need tools to market their products, one of which is a form of e-commerce. E-commerce is an e-business application that deals with transactions, marketing, electronic data transportation, and so on. This study aims to determine the strategies that can be used by e-commerce users in marketing or selling their products. The research method used in this journal is a qualitative descriptive study, which uses literature studies using journals, books, or websites that support the research title.